The answer is (-21, 13) for The second endpoint.
Let's start by calling the known endpoint L and the unknown K. We'll call the midpoint M. In order to find this, we must first note that to find a midpoint we need to take the average of the endpoints. To do this we add them together and then divide by 2. So, using that, we can write a formula and solve for each part of the k coordinates. We'll start with just x values.
(Kx + Lx)/2 = Mx
(Kx + 1)/2 = -10
Kx + 1 = -20
Kx = -21
And now we do the same thing for y values
(Ky + Ly)/2 = My
(Ky + 7)/2 = 10
Ky + 7 = 20
Ky = 13
This gives us the final point of (-21, 13)